UTILIZATION OF FLAVONOIDS FROM VEGETABLES AND FRUITS AS IMMUNE SYSTEM ENHANCERS DURING A PANDEMIC IN PANIKI VILLAGE, MAPANGET DISTRICT, MANADO CITY (Proceedings of the International Conference on Digital Health and Telemedicine, 2024)
Along with the end of the COVID-19 pandemic, various problems have emerged, which health being a sector that requires more attention for recovery. People believe that consuming immune system enhancing supplements can help maintain health, but the issue of affordability poses another challenge for them. Maintaining a strong immune system can be achieved in a simple and cost-effective way, namely by incorporating vegetables and fruits into the diet. These natural foods contain nutrients that have the potention to act as antioxidants, anti-inflammatories, and detoxifiers. The benefits of antioxidants are believed can enhance and sustain the immune system, particularly during pandemic. Flavonoids, which are found abundantly in fruits and vegetables, can be extracted by soaking them in suitable solvents. Flavonoids are soluble in polar and semipolar solvents, including water. Community education on the utilization of flavonoids was conducted in Paniki Village, Mapanget District, using direct learning and simulation methods. The target audience consisted of productive individuals aged 20-40 years and teenagers. The evaluation, has been held through direct interviews 5 days after the activity, revealed an increased knowledge among the participants regarding the utilization of vegetables and fruits, as well as an improved understanding of the processing methods to optimize the nutritional benefits they provide. Based on these findings, it can be concluded that direct learning dan simulation activities effectively enhance the knowledge of flavonoids utilization from vegetables and fruits among the productive age residents and adolescents in Paniki Village.
Keywords: flavonoids; immune system; community education